Improvement in the environmental management of solid urban waste in small nea towns. The Leandro N. Alem case - Berent, Mario Rubén (2004)
Fil: Berent, Mario Rubén. Universidad Nacional del Nordeste. Facultad Arquitectura y Urbanismo; Argentina.